PUTTING THE PIECES TOGETHER: INVESTIGATING THE ROLE OF 3 LANGUAGE SKILLS TO DEVELOP MIDDLE SCHOOL LEARNERS’ WRITING PROFICIENCY - Mather, Nazarana (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Writing can be used as a tool to develop learners’ speaking, listening, and reading skills and vice versa. This can be achieved by the teacher providing opportunities for learners to speak about their writing, as this allows them to rehearse the language that they will use in their texts, and perhaps develop appropriate vocabulary, and to exchange ideas with their peers before committing the words to paper [Grave, 1983]. The teacher could further establish a balance between talk and writing, set up and manage talk in pairs and groups, schedule individual teacher time and use writing for oral presentations [Graves, 1983]. Reciprocally, speaking is an important tool for scaffolding learners’ writing. Adding to this, the more learners read, the more their thinking skills, linguistic knowledge and understanding of the structure of different genres will increase, thus their writing will improve. Although the teaching of reading and writing should be integrated, each should be given equal attention, as both are important literacy skills required for effective functioning in modern society and, according to Grabe [2003], if they are taught together, the result can lead to more effective learning. This relationship between writer, reader and thinker is integral to the writing process [Mather, 2019]. This purpose of this study is to explore how speaking, reading, and thinking are used to scaffold learners’ writing skills in primary school. For this exploratory case study, two schools participated in this study. Learners completed an activity-based questionnaire, the two teachers were interviewed, writing lessons were observed and a sample of the learners’ writing with their teachers’ feedback was analysed using document analysis. Lesson and interview recordings were transcribed, and the transcriptions were analysed with the observation schedule using content analysis, as were the learners’ responses to the questionnaire. It was found that there are multiple strategies that teachers use to scaffold learners’ writing using reading, thinking, and speaking skills. It was concluded that the teacher’s knowledge of integrating speaking, reading, and thinking skills play a pivotal role in developing their learners’ writing skills. Writing